Desempenho de wetlands construídos preenchidos com resíduos da construção civil na remoção de matéria orgânica, ibuprofeno, paracetamol e etinilestradiol de esgotos sanitários - Marcelino, Gabriela Ribeiro (2019)
The objective of this research was to evaluate the performance of three Constructed Wetlands (CW) of vertical flow (0.5 m x 0.4 m x 0.3 m) filled with different substrates: expanded clay (CW-A), expanded clay and porcelain (CW-AP) and brick (CW-T) in the treatment of synthetic effluent simulating pretreated sewage (low organic load <250 mg L-1). The macrophyte Pistia stratiotes, known as water lettuce, was used as vegetation cover in the three WC. Through the SEM and SED analyzes, it was possible to observe similar porosities in clay and porcelain (inside part) and higher porosity and contact surface in the brick. The main chemical compounds found in these materials were SiO2, Al2O3 and Fe2O3, corresponding to clay materials. The parameters pH, temperature, OD, EH, TKN, N-NH3, nitrite, nitrate, TP, COD, paracetamol, ibuprofen and ethinylestradiol were determined in samples of the influent and effluent of the CW during 188 days of operation. The CW-AP system was more efficient in the removal of organic matter (COD) with 75%. CW-T was the most efficient system for the removal of TKN (73%), N-NH3 (70%) and TP (46%). The CWA system presented higher performance in nitrate removal (51%). Micropollutants were satisfactorily removed, with maximum removals of 92% of ibuprofen in CW-A, 95% of acetaminophen in CW-A, and 69% of ethinyl estradiol in CW-AP. Greater TN and TP accumulation was observed in the roots of the plants compared to the leaves, and greater accumulation of TP than TN in the substrates. The systems with the greatest efficiencies were CW-A and CW-T.